An introduction to sadharanikaran model of communication - Adhikary, Nirmala Mani (Bodhi: An Interdisciplinary Journal, 2010)
This article describes sadharanikaran model of communication (SMC) and outlines its fundamentals. The article initially discusses the concept of ‘sadharanikaran' as conceived in Hindu poetics acknowledging its relevance for the modern discipline of communication. And, it also presents an account of the background upon which the model was developed and proposed. The descriptive part of the article is primarily indebted to Natyashastra and Vakyapadiya DOI: 10.3126/bodhi.v3i1.2814 Bodhi Vol.3(1) 2009 p.69-91